The paradigm of informational behavior as an alternative to understand the informational phenomena in Latin America - Berrío-Zapata, Cristian [UNESP]; Moreira, Fabio Mosso [UNESP]; Sant'Ana, Ricardo Cesar Gonçalves [UNESP]; Ortega, María Liliana Muñoz (Universidad de Antioquia, 2016)
Documentation science, a predecessor of information science, historically neglected to study a common person. As a product of the Fordist Era, documentation science supposed the value of any information on behavior was its technical and economic nature. In contrast, this article presents some of the contributions of the paradigm of informational behavior, which moves away from this trend, and it emphasizes on a formal standardized information system to study a common use and that user's day-to-day life. Informational Behavior develops an ecological and evolutionary epistemology. Knowledge workers are no longer the only Community worthy of being studied. Today studies research communities, closed niches, excluded groups, and representative populations of vast human majorities. For information science, in developing countries, this is an opportunity to understand situation update information on users from other perspectives and critically evaluate imported concepts like the digital divide, which is based on, and utilitarian technocentric vision of the classic paradigm.
El paradigma de Comportamiento Informacional como alternativa para comprender los fenómenos informacionales en América Latina
Keywords: Digital divide; ICT; Information Behavior; Information science